1993
DOI: 10.1128/aem.59.12.4121-4128.1993
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of human bifidobacterial strains to cultured human intestinal epithelial cells and inhibition of enteropathogen-cell interactions

Abstract: Thirteen human bifidobacterial strains were tested for their abilities to adhere to human enterocyte-like Caco-2 cells in culture. The adhering strains were also tested for binding to the mucus produced by the human mucus-secreting HT29-MTX cell line in culture. A high level of calcium-independent adherence was observed for Bifidobacterium breve 4, for Bifidobacterium infantis 1, and for three fresh human isolates from adults. As observed b3 scanning electron microscopy, adhesion occurs to the apical brush bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
131
0
11

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(155 citation statements)
references
References 45 publications
13
131
0
11
Order By: Relevance
“…That is to say, delayed colonization of bifidobacteria appeared to lead to the unusual growth of Enterobacteriaceae in the AT subjects. This is consistent with the data in some previous studies that showed an antagonistic relationship between Bifidobacteria and Enterobacteriaceae (Bernet et al, 1993;Gibson & Wang, 1994;Hutt et al, 2006). It is interesting that the development of gastrointestinaltract microbiota in the CD infants followed similar, although weaker, trend to AT infants, namely, less bacterial diversity in the first week, delayed colonization of bifidobacteria, and overgrowth of Enterobacteriaceae.…”
Section: Discussionsupporting
confidence: 91%
“…That is to say, delayed colonization of bifidobacteria appeared to lead to the unusual growth of Enterobacteriaceae in the AT subjects. This is consistent with the data in some previous studies that showed an antagonistic relationship between Bifidobacteria and Enterobacteriaceae (Bernet et al, 1993;Gibson & Wang, 1994;Hutt et al, 2006). It is interesting that the development of gastrointestinaltract microbiota in the CD infants followed similar, although weaker, trend to AT infants, namely, less bacterial diversity in the first week, delayed colonization of bifidobacteria, and overgrowth of Enterobacteriaceae.…”
Section: Discussionsupporting
confidence: 91%
“…1999). It is interesting to note that the pattern of killing activity displayed by L. helveticus strain KS300 against S. typhimurium resembles the patterns of killing activity previously described for probiotic Lactobacillus strains including Lactobacillus johnsonii La1, L. rhamnosus GG, L. rhamnosus strain GR-1, Lactobacillus casei Shirota strain YT9029, and L. casei strain DN-114 001 (Bernet et al 1993;Hudault et al 1997;Fayol-Messaoudi et al 2005), and Lactobacillus acidophilus strain LB (Coconnier et al 1997). These Lactobacillus strains killed S. typhimurium mainly by the action of secreted nonlactic acid molecules present in CFCSs (Silva et al 1987;McGroarty and Reid 1988;Bernet-Camard et al 1997;Coconnier et al 1997;Fayol-Messaoudi et al 2005).…”
Section: Discussionsupporting
confidence: 68%
“…16,18 Bifidobacterium and Lactobacillus have been long known to produce bacteriocines and unfavorable adhesion conditions for Gram-positive species. 19,20 In the present study, all three tested compounds produced a reduction in the Gram-positive population in favor of an expansion of Bifidobacterium and Lactobacillus. However, the specific bacterial count of Bacteroides and Clostridium significantly decreased only in the group treated with the synbiotic.…”
Section: Discussionsupporting
confidence: 46%